Trimethoprim-sulfamethoxazole (TMP/SMX) potentiates indinavir nephrotoxicity - Araujo, Magali de [UNIFESP] (2002)
Objectives: Indinavir is a widely prescribed protease inhibitor in the treatment of HIV infection. It has been associated with nephrolithiasis, crystalluria and tubulointerstitial nephritis. Nelfinavir is another protease inhibitor used successfully in AIDS treatment. The objective of this study was to evaluate the effect of both indinavir and nelfinavir individually, and in association with trimethoprim-sulfamethoxazole (TMP/SMX), on renal function in Wistar rats.Methods: Doses of indinavir (80 mg/kg body weight [BW] daily), nelfinavir (75 mg/kg BW daily) and TMP/SMX (100 mg TMP/kg BW daily) were given by gavage for 15 days. Seven groups were studied: control, vehicle, TMP/SMX, indinavir, indinavir+TMP/SMX, nelfinavir, and nelfinavir+TMP/SMX.Results: No changes were observed in body weight, urine volume and blood pressure. The vehicle group did not differ from the control group. TMP/SMX induced a small decrease in inulin clearance with no tubular alterations. Indinavir decreased inulin clearance (indinavir: 0.48 +/- 0.03 vs control: 0.93 +/- 0.08, P<0.001) and renal blood flow (indinavir: 6.2 +/- 0.2 vs control: 8.0 +/- 0.3, P<0.05). These effects were potentiated by TMP/SMX, which produced high vasoconstriction associated with alterations in tubular functions, characterised by increased fractional excretion of sodium (indinavir+TMP/SMX: 1.14 +/- 0.16 vs control: 0.39 +/- 0.07, P<0.01). Nelfinavir either alone or in combination with TMP/SMX did not change the renal function of the rats.Conclusion: These results suggest that indinavir nephrotoxicity in rats is potentiated by TMP/SMX and that nelfinavir alone or in combination with TMP/SMX is not nephrotoxic.